Gender Based Violence and the Global Gendered Viewpoint Approaches to Building a Peaceful South Africa - Andrew Osehi Enaifoghe (Journal of Social and Development Sciences, 2019)
This study looks at the prevalence of gender violence in South Africa particularly, and argues to support a gendered perspective as an approach with the inclusion of women in an effort to address or resolve violence against women. The UNSCR-1325 reaffirmed the significance of gender integration at all levels of peace and security agenda, the purpose underlined in the declaration shows a slow affirmation among international organisations. The effect of gender based brutality is a significant human rights infringement with real social and formative effects for overcoming viciousness. On an individual level, sexual based violence can lead to mental injury, and can have both psychological social and physical ramifications for survivors. Therefore, the argument set forward in support of a gendered viewpoint to deal with violence and peace-building originated from a classified arrangement of political characters, from a collection of controls, with various political sentimentalities and distinctive prescribed techniques for conflicts intervention. Furthermore, the global gendered perspective intervention is also assessed as a strategy by exploring various approaches to deal with global gender-based conflict. The approaches are considered instrumentalist in their various approaches, as they consider women to be instrumental in accomplishing a maintainable peace, but dismissing the issue of how peace can improve the situation of violence against women, and not taking into consideration the issues of gender based violence. This tremendously fails to discourse and address structural disparities and power crescendos or dynamics that underpinned gender discrimination. Findings in this study shows that, there is a need for gendered perspective to address violence and build peace in various civil societies, while taking into account the socio-economic effect of gender violence. Peace and Security plan is goal-oriented and transformative in its discourse. Therefore, it requires women's contribution to fight gender violence at all levels.